Ethnomathematics Integration to Enhance Preschoolers’ Early Math Problem-Solving Skills: A Qualitative Case Study - Ndeot, Felisitas; Hartati, Sofia; Hapidin, Hapidin (Hexagon: Jurnal Ilmu dan Pendidikan Matematika, 2025)
This study investigates how integrating ethnomathematics into early childhood education can improve the early math problem-solving skills of preschoolers aged 5–6 years. Conducted in Manggarai, Indonesia, the research employed a qualitative case study approach to explore learning activities infused with local cultural elements, including the spider-web rice field layout (lingko), traditional Manggarai houses (mbaru niang), and woven fabric patterns (songke). These cultural artifacts were adapted into problem-based learning tasks to develop children’s mathematical thinking. Data were collected through classroom observations, semi-structured interviews with the teacher, and documentation of children's learning outcomes, such as photographs, drawings, and activity records. The data obtained from classroom observations, teacher interviews, and documentation of children's learning outcomes are transcribed verbatim. The coding process is conducted inductively, meaning the codes are not predetermined but emerge from the data itself. The researchers read each transcript and documentation repeatedly to identify statements, actions, or interactions relevant to problem-solving skills. Codes that have similar meanings are then grouped into categories. These subthemes are analyzed further to identify the main theme that reflects the phenomenon as a whole. After the main theme is formed, the researcher interprets the findings by relating them to the research objectives, research questions (RQ1 and RQ2), as well as previous theories or findings. The findings reveal that embedding familiar cultural representations in mathematics instruction enhanced children’s problem-solving strategies, persistence, and conceptual understanding. Moreover, using culturally relevant contexts increased children’s engagement and confidence. This study highlights the importance of integrating local wisdom into early math education as a pathway to inclusive and resilient learning environments.